The Effect of Free Cash Flow, Company Size, Profitability and Liquidity on Debt Policy for Manufacturing Companies Listed on IDX in 2016-2019 Periods - Adam Afiezan; Giovanni Wijaya; Priscilia Priscilia; Cindy Claudia (Budapest International Research and Critics University, 2020)
The purpose of this research is to analyze and study the effect of Free Cash Flow, Company Size, Profitability and Liquidity on the Debt Policy of manufacturing companies listed on the IDX in 2016-2019. This type of research is a quantitative descriptive one. Of the 169 populations, only 83 samples met the criteria. Data processing with multiple linear regressions. The partial test results are only liquidity that has a negative and significant effect on debt policy, while Free Cash Flow, Company Size and Profitability have no effect on debt policy. Simultaneous test results where Free Cash Flow, Company Size, Profitability and Liquidity have an influence on debt policy with the results of the determination coefficient of 0.589 which means as much as 58.9% of the variation in debt policy that can be explained by variables (FCF, company size, profitability and liquidity) where the remaining 41.1% is influenced by other factors.